Cellulose nanocrystals extracted from hemp agro-waste as a potential coating for titanium medical devices - Heacock, Jesse Andrew, author; Li, Yan Vivian, advisor; Kipper, Matt, committee member; Liu, James, committee member (Colorado State University. Libraries, 2024)
Increases in biowaste worldwide have created a unique opportunity to extract natural polymers for a variety of uses. Over the last few decades, hemp has increased in popularity as a desirable industrial agricultural plant. Increases in hemp production for commercial product use have increased the amount of hemp agro waste (HAW). This agro-waste is a potentially great source for extraction of the natural polymer cellulose and the creation of a circular economy. Cellulose can be found ubiquitously in plants and has gained great interest as an alternative to synthetic polymers. In this work, cellulose nanocrystals (CNCs) were extracted from HAW using a one-step ammonium persulfate (APS) oxidation method. APS oxidation was used due to its reduction in hazardous wastes, making it a more environmentally friendly method for CNC extraction compared to other chemical methods. HAW, specifically the woody core of hemp known as hurd, underwent CNC extraction and the properties of the final product were analyzed. Depending on the initial source and method of extraction, CNCs properties have been shown to vary, creating a potential for selectivity when applying CNCs for different uses. It was found that changes in reaction time directly impact CNCs size, surface properties, final product mass, and hydrophilicity. Of note, as reaction time increased from 8 hours to 48 hours, the size of the nanocrystals significantly decreased in length and width. While other properties, such as mechanical strength, morphology, surface charge, and cytotoxicity, underwent no statistically significant changes due to increases in reaction time. The results suggest that HAW is a good source for CNC extraction and that changes in APS oxidation can allow for selective tuning of some CNC properties.
Keywords: biowaste; cytotoxicity; Young's modulus of elasticity; cellulose nanocrystals; ammonium persulfate; force distance spectroscopy